2018
DOI: 10.1111/bcp.13595
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of voriconazole and CYP2C19 polymorphisms for optimizing dosing regimens in renal transplant recipients

Abstract: Using a combination of CYP2C19 genotype and postoperative time to determine the initial voriconazole dosing regimens followed by therapeutic drug monitoring could help to advance individualized treatment in renal transplantation patients with invasive fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 43 publications
(66 reference statements)
11
56
0
Order By: Relevance
“…The initial database search yielded 152 publications, and after selection, a total of 16 studies involving 1411 participants met the inclusion criteria [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The population characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial database search yielded 152 publications, and after selection, a total of 16 studies involving 1411 participants met the inclusion criteria [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The population characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…CYP 2C19 genotyping data were included in 11 articles [12, 14-18, 21, 23-26]. Among the 16 publications describing a population pharmacokinetic model for voriconazole, 11 described studies conducted in adult participants, [11][12][13][14][15][16][17][18][19][20][21] whereas four of the studies were conducted in pediatric populations, [22][23][24][25] and the remaining study by Friberg et al [26] included both adult and pediatric patients. The studied populations consisted of healthy volunteers and patients who were administered voriconazole for the treatment or prophylaxis of fungal infections, possibly accompanied by additional pathologies, including pulmonary diseases, organ transplant, and hematological malignancies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that CYP2C19 polymorphisms extensively affected voriconazole plasma concentration. 14,19,[48][49][50][51] A recent prospective study in renal transplant recipients 52 showed that CYP2C19 polymorphisms significantly affected the CL of voriconazole; PM patients had significantly higher plasma concentration than both IM patients and EM patients. However, CYP2C19 polymorphisms, it did not affect the pharmacokinetic parameters of voriconazole in this study.…”
Section: Discussionmentioning
confidence: 99%